Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1186/s13018-020-01765-9
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the inflammation/immune indexes and deep venous thrombosis (DVT) incidence rate following tibial plateau fractures

Abstract: Objective To determine the relationship between inflammation/immune-based indexes and deep venous thrombosis (DVT) incidence rate following tibial plateau fractures Methods Retrospective analysis of a prospectively collected data on patients undergoing surgeries of tibial plateau fractures between October 2014 and December 2018 was performed. Duplex ultrasonography (DUS) was routinely used to screen for preoperative DVT of bilateral lower extremities. Data on biomarkers (neutrophil, lymphocyte, monocyte, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 34 publications
2
34
0
Order By: Relevance
“… 4 In addition, in a study of 1179 patients by Liu and colleagues, a similar viewpoint was confirmed. 12 In the present study, we had the same conclusion, and found both factors are risk factors of DVT after lumbar fusion surgeries, further confirming the conclusion of previous literature. D-dimer, as a degradation product of cross-linked fibrin, work as an indicator of both coagulation- and fibrinolysis activation and an elevated D-dimer level is associated with an increased risk in thrombin formation.…”
Section: Discussionsupporting
confidence: 91%
“… 4 In addition, in a study of 1179 patients by Liu and colleagues, a similar viewpoint was confirmed. 12 In the present study, we had the same conclusion, and found both factors are risk factors of DVT after lumbar fusion surgeries, further confirming the conclusion of previous literature. D-dimer, as a degradation product of cross-linked fibrin, work as an indicator of both coagulation- and fibrinolysis activation and an elevated D-dimer level is associated with an increased risk in thrombin formation.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies have investigated the risk factors for perioperative DVT after tibial fractures, 2 , 5 such as body mass index, pre-existing diabetes, delay to ultrasonography, platelet count, neutrophil count, older age, hyponatremia, and prolonged surgical time 1 3 . Surgeons always pay attention to fracture classification and build an association between tibial plateau fracture and DVT, 1 , 2 tibial shaft fracture and DVT, 3 and distal tibial fracture and DVT. 4 However, the end of the fracture line is the actual injury plane, and the effect of the plane on perioperative DVT has not been explored.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of DVT varies across locations. The incidence of perioperative DVT in patients with tibial fractures is 4.7 to 16.3% in the tibial plateau, 1 , 2 13.3% in the shaft, 3 and 1.7% in the distal tibia. 4 The incidence of DVT in the proximal segment was higher than that in the distal segment.…”
Section: Introductionmentioning
confidence: 99%
“…Acute DVT causes a systemic in ammatory response characterized by elevated in ammatory factors and temporal accumulation of in ammatory cells including white blood cells [43,44]. Dawei Liu et al studied 1179 patients of tibial plateau fractures, and found that platelet and neutrophil count were independently associated with elevated D-dimer levels [45]. Moreover, data from 84 patients with lung cancer showed the accumulation of massive neutrophils in the in ammation sites leads to embolism and thrombosis which resulting poor prognosis [46].…”
Section: Discussionmentioning
confidence: 99%